Primary healthcare use during follow‐up after curative treatment for colorectal cancer. (10th October 2016) - Brandenbarg, D.; Roorda, C.; Groenhof, F.; de Bock, G. H.; Berger, M. Y.; Berendsen, A. J.
Abstract : The rising number of colorectal cancer (CRC) survivors is likely to impose a burden on healthcare systems. Effective resource allocation between primary and hospital care to ensure ongoing high‐quality care is under discussion. Therefore, it is important to understand the current role of GPs during follow‐up care of CRC. This study explores the primary healthcare use of patients 2–6 years after CRC treatment. Annual rates of face‐to‐face contacts, prescribed medication and referrals were compared between CRC patients and age, gender and GP matched controls in a historical prospective study. Reasons for contacts and prescribed medication were compared based on International Classification of Primary Care and Anatomical Therapeutic Chemical (ATC) Classification System codes, respectively. Negative binomial regression models and non‐parametric test were used. Patients showed significantly more face‐to‐face contacts in the 2nd (63%), 3rd (32%) and 6th (23%) year, more drug prescriptions in the 2nd, 3rd and 6th year, and more referrals in the 2nd and 5th year after diagnosis. Differences in contacts and medication were related to the alimentary tract, blood and blood‐forming organs, and psychological problems. This study suggests that GPs already play a substantial role during CRC follow‐up and that there may be scope for formal services to be incorporated into the current model of GP care.